Routine Lower Extremity Screening Ultrasound Protocols in Trauma Patients Are Not Cost Effective. Issue 7 (July 2022) - Miles, M. Victoria P.; Brown, Caroline N. H.; Webster, Cassidy C.; Armistead, Charles; Gilchrist, S. Austin; Everett, Hayley; Wilson, Andrew; Maxwell, Robert
Background: Despite prophylaxis, deep vein thrombosis (DVT) and pulmonary embolism remain dreaded complications following traumatic injury and are associated with significant morbidity and mortality. Screening ultrasound (US) protocols have been employed in trauma centers for early detection of lower extremity (LE) deep venous thrombosis. We hypothesized that screening lower extremity venous duplex US would not prove cost effective in our trauma population who receives early pharmacologic prophylaxis. Methods: Data was collected for one year on all adult trauma patients admitted to the trauma service from December 2019 to 2020. DVT screening US was obtained at 3 days after admission for patients with long bone or pelvic fracture, spinal cord injury, immobility, and/or spinal fracture requiring surgery. Screening US was obtained at 7 days for all others and repeated weekly until discharge. Data was retrospectively collected and analyzed. Results: Exactly 1365 patients met inclusion criteria with median ISS 12 (IQR, 9-17), median age 56 (IQR, 36-73 years), and with majority blunt injuries (90.7%). A total of 1369 screening US were performed finding 27 DVTs (2%). The total cost of screening for the year analyzed amounted to over 270, 000 with 50.7 screening US needed to detect 1 DVT. This resulted in an average screening cost of over 10, 000 for the detection of a single DVT. Discussion: In trauma patients receiving early pharmacologic prophylaxis, routine LE screening US protocols to detect LE DVT are not cost effective.